Total Phenolic, Total Flavonoid Content and in vitro Sun Protection Factor test of Arabica Coffee Leaves Extract (Coffea arabica L) - Fatmawati, Sofia; Sjahid, Landyyun Rahmawan; Utami, Nadiyya Maulida; Kartini, Kartini (Journal of Science and Technology Research for Pharmacy, 2022)
Background: Arabica coffee leaf (Coffea arabica L.) is a well-known plant by the Indonesian people because it has many benefits apart from being a drink. Coffee leaves are known to have good antioxidant activity. The use of antioxidants in sunscreen preparations can prevent various diseases caused by UV radiation from UV rays’ sunlight. Aim: This study aims to determine the phenol content, the flavonoid content and the value of Sun Protection Factor (SPF) from differences between solvent extracts of arabica coffee leaves (Coffea arabica L.). Method: The extraction method used was maceration with solvents: 70% ethanol, 96% ethanol and methanol. Determination of phenol content was carried out using the Folin ciocalteu method. Determination of flavonoid content was done by the AlCl3 method. SPF value is based on the Mansur equation from absorbance scanning using UV Spectrophotometry. Result: The results obtained were the highest phenol and flavonoid content is in the methanolic extract of arabica coffee namely 62.371 ± 0.47 mgGAE/g and 8.6707 ± 0.04 mgQE/g. In the SPF test, the highest value was obtained from 70% ethanol extract of 5.0593 ± 1.28 at 100 ppm extract concentration with intermediate protection category. Conclusion: Arabica coffee leaves have the potential as an active ingredient in herbal sunscreens